MENGEMBANGKAN KECERDASAN INTEGRATIF (Catatan Bagi Upaya Pengembangan Kecerdasan Manusia) - Mahmudah, Siti (Psikoislamika : Jurnal Psikologi dan Psikologi Islam, 2005)
AbstractToday education has not been successful to make and develop the students become good citizen. This is because, our modern education today has emphasized only on intellectual intelligence while the others are neglected. As the result, there are many students that have high intellectual intelligence but their characters are bad. Education should include developing intellectual intelligence, emotional intelligence, and spiritual intelligence in balance. Education should be able to form character of the students to have multiple intelligence so that they can solve all the problem in their life. For that, the policy of education program should be directed and emphasized on spiritual values and emotional values as the basis to obtain intellectual intelligence, and this must be one packet in educational process that cannot be separated.Keywords: intelligent potential, education and integrative